Peran Ireland Palestine Solidarity ‎Campaign Terhadap Kebijakan Larangan Impor Produk Israel Tahun 2018 - Fiani Nurmalasari; Ida Susilowati (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2021)
Violations of Human Rights and International Humanitarian Law of Israel against Palestine have generated a lot of attention from the state and the world community, including Ireland. The existence of historical similarities made Ireland take a stance to support Palestine in gaining independence from Israeli colonization. IPSC (Ireland Palestine Solidarity Campaign) as one of the CSOs (Civil Society Organizations) in Ireland is one of the actors that plays an active role in pressuring the Irish government to pass the Bill on the Prohibition of Importing Israeli Products, namely through the BDS (Boycott, Divestment and Sanctions) movement. Based on this, this study aims to understand the significance of the role of transnational networks carried out by IPSC as CSOs in the study of International Relations in terms of the framework of the Transnational Advocacy Network (TAN) in particular